Case report: tracheobronchial diverticulum, a potential risk for diving? - Qing, Long; Wang, Yan; Zhang, Meng; Pu, Qinqin; Cai, Wanwan; Pan, Yaping; Xia, Delin (Frontiers in Medicine, 2024)
Tracheobronchial diverticulum(TBD) is an asymptomatic, benign cystic lesion outside the lumen of the trachea and bronchus. This is the first report case of a SCUBA(Self Contained Underwater Breathing Apparatus) diver diagnosed with TBD, which is a potential risk to diving. No literature or guideline is available so far on the diving fitness for patients with congenital or acquired TBD condition. A healthy 26-year-old male professional diver has records of SCUBA diving up to depth of 40 meters sea water. He did not have any diving-related injuries or symptoms during his career and had no history of smoking, drinking, or other special illnesses except for a COVID-19 infection. A tracheal diverticulum was found accidentally by computed tomography(CT), but its communication with the trachea was not clear initially. Therefore, high-resolution CT and electronic bronchoscopy were done to clarify the situation of diverticulum and identify the diving risk. High-resolution CT showed a possible opening of diverticulum, but this was not seen under electronic bronchoscopy. Although a potential opening was showed in high-resolution CT, the lack of visual bronchoscopic evidence made it likely to be a dead cavity. As there is a higher theoretical risk of barotrauma during decompression, leading to pneumomediastinum, hemorrhage or arterial gas embolism, the current clinical consensus is that air-containing tissue should be regarded as relative contraindications to diving. In overall, it is recommended that the diver should dive carefully and avoid ascending too rapidly.